The Role of Oxygen Intermediates in the Retention Time of Diacetyl Adaptation in the Nematode Caenorhabditis elegans. Issue 8 (3rd June 2013) - Nishino, Asuka; Kanno, Ryo; Matsuura, Tetsuya
ABSTRACT Continuous presentation of the odorant diacetyl to the nematode Caenorhabditis elegans causes a decrease in the level of chemotactic response to diacetyl. This decline in response is caused by diacetyl adaptation. When wild‐type nematodes were maintained at 15°C after pre‐exposure to diacetyl, diacetyl adaptation did not continue up to 2 hr. Adaptation continued up to 6 hr in nematodes bred at 20°C, and it continued beyond 12 hr in nematodes bred at 25°C. These results indicate that the retention time of diacetyl adaptation is dependent on the environmental breeding temperature and suggest that moderate oxygen signals are required for maintaining the attenuated response to diacetyl because of the correlation between breeding temperature and production of oxygen intermediates. When isp‐1 and clk‐1 mutants, which show reduced rates of oxygen intermediate production, were maintained at 20 and 25°C after pre‐exposure to diacetyl, the mutants showed a shorter retention time of diacetyl adaptation compared with that of wild‐type nematodes. When gas‐1 and mev‐1 mutants, which have a hypersensitive response to oxidative stress, were maintained at 15 and 20°C, they showed a longer retention time of adaptation, that is, adaptation continued beyond 2 and 12 hr, respectively. When wild‐type nematodes were maintained on plates that included 0.05% α‐lipoic acid, which suppresses production of oxygen intermediates, the retention time of adaptation did not continue up to 6 hr in nematodes bred at 20°C and up to 12 hr in nematodes bred at 25°C. These results support the possibility that oxygen intermediates contribute to retention time for diacetyl adaptation in the nematode C. elegans. J. Exp. Zool. 319A: 431–439, 2013. © 2013 Wiley Periodicals, Inc.